Floating hutongs life to diminishing Confucian courtyard narratives in Jinan, China - Weihan Rong; Azizi Bahauddin; Mengyun Xiao (Journal of Asian Architecture and Building Engineering)
Confucianism has shaped traditional Chinese urban patterns and sustainable housing development, resulting in a fusion of architectural styles across China and neighbouring regions. As previous research has focused on the physical and environmental aspects of sustainable urban environments and housing, the evolution of spatial narratives has been overlooked. This study explores the significance and influence of Confucian narratives in urban streets and juxtaposed courtyard houses, specifically in the Mingfucheng area of Jinan, Shandong Province. By employing a qualitative approach through semi-structured interviews with residents, the study explores architecture and hutong spaces. The findings highlight the positive impact of Confucian concepts on residents’ lives, spatial behaviour, and spirituality. It also addresses the challenges and opportunities in the process of urbanisation and rural revitalisation. This research provides a narratological perspective on the sustainability of culturally influenced traditional architecture, contributes to the knowledge on courtyards and hutongs, and suggests sustainable strategies for architectural culture and heritage conservation.